ViceROI: Catching Click-Spam in Search Ad Networks - Dave, Vacha; Guha, Saikat; Zhang, Yin (Proceedings of the 20th Conference on Computer and Communications Security (CCS), 2013)
Click-spam in online advertising, where unethical publishers use malware or trick users into clicking ads, siphons off hundreds of millions of advertiser dollars meant to support free websites and apps. Ad networks today, sadly, rely primarily on security through obscurity to defend against click-spam. In this paper, we present Viceroi, a principled approach to catching click-spam in search ad networks. It is designed based on the intuition that click-spam is a profit-making business that needs to deliver higher return on investment (ROI) for click-spammers than other (ethical) business models to offset the risk of getting caught. Viceroi operates at the ad network where it has visibility into all ad clicks. Working with a large real-world ad network, we find that the simple-yet-general Viceroi approach catches over six very different classes of click-spam attacks (e.g., malware-driven, search-hijacking, arbitrage) without any tuning knobs.